Sharing is caring: Exploring digital knowledge sharing and SMEs’ green innovative performance through the mediating role of green technology dynamism - Muhammad Farhan Jalil; Abu Hassan Bin Md Isa; Dayang Affizzah Binti Awang Marikan; Mohamad bin Jais (International Journal of Engineering Business Management, 2025)
In the era of digitalization, knowledge sharing is considered crucial to understanding the environmentally sustainable performance of Small and Medium Enterprises (SMEs). Despite this, there is a notable absence of empirical evidence in the academic literature addressing this relationship. Therefore, the purpose of this study is to examine the impact of digital knowledge sharing (both internal and external) on green innovative performance. Additionally, the study seeks to determine whether these relationships are mediated by the green technology dynamism of SMEs in Malaysia. Data were collected from 294 Malaysian SME owners and managers who completed online, self-administered surveys. The study constructs, adapted from earlier research, were measured using validated measurement scales. Structural equation modelling was employed to analyse the data and test the hypotheses (utilizing AMOS 24.0). Bootstrapping of confidence intervals was conducted to identify mediating effects. The study’s results revealed a positive and significant association between digital knowledge sharing (both internal and external) and the green innovative performance of SMEs. Furthermore, the data analysis confirmed that green technology dynamism serves as a complementary mediator in the relationship between digital knowledge sharing (both internal and external) and green innovative performance. The findings of this study carry both theoretical and practical implications for academics and SME owners/managers. Green innovative performance, strengthened by green technological dynamism, can help SMEs grasp and implement the significance of digital knowledge sharing in their administrative operations. Consequently, they can transform into eco-innovative entities, contributing positively to the environment, economy, and society.